2021
DOI: 10.1089/apc.2020.0262
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in an Urban Cohort of Adolescents Living with Human Immunodeficiency Virus: Characteristics and Outcomes in Comparison to Adults

Abstract: Adolescents (13-24 years of age) account for more than one-fifth of new HIV diagnoses yearly, and the United States has one of the highest rates of adolescent pregnancy among high resource countries. However, there is limited information on the characteristics and outcomes of adolescents living with HIV (ALWHIV) during pregnancy and differences with pregnancy in adults living with HIV. We performed a retrospective cohort study to compare demographic characteristics, HIV viral suppression, and pregnancy outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(31 reference statements)
0
3
1
1
Order By: Relevance
“…Our results are in line with previous studies addressing the reproductive health of WLWPHIV, which in different settings have shown that they become pregnant at an early stage, with a high percentage of unintended pregnancies. 5 , 25 , 26 The median age at first delivery in our study was 20 years, in contrast with data from Spanish Statistical Office (INE) 27 which show a progressive increase of mean age of women in our country at first delivery from 29.1 years in 2000 to 31.1 years in 2020. Despite the fact that access to sexual health and contraceptive drugs are at least partially covered by the health care system in Spain, accessibility for adolescents is suboptimal; most clinics are staffed in the mornings, few clinics provide care anonymously, and most contraceptives require patient copayment.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results are in line with previous studies addressing the reproductive health of WLWPHIV, which in different settings have shown that they become pregnant at an early stage, with a high percentage of unintended pregnancies. 5 , 25 , 26 The median age at first delivery in our study was 20 years, in contrast with data from Spanish Statistical Office (INE) 27 which show a progressive increase of mean age of women in our country at first delivery from 29.1 years in 2000 to 31.1 years in 2020. Despite the fact that access to sexual health and contraceptive drugs are at least partially covered by the health care system in Spain, accessibility for adolescents is suboptimal; most clinics are staffed in the mornings, few clinics provide care anonymously, and most contraceptives require patient copayment.…”
Section: Discussioncontrasting
confidence: 96%
“…Subsequent studies should additionally address the challenges of counseling adolescent parents living with HIV about feeding choice, given they are at increased risk for disengaging from care. 40 Moreover, the authors recognize that transgender men and gender nonbinary individuals may be birthing parents, and may choose to feed at the chest. 41 , 42 Unfortunately, because the term “breastfeeding” was utilized in our survey, the results cannot necessarily be extrapolated to apply to chestfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, 3 out of every 10 infected individuals are women who acquired the virus through sexual transmission 2 . Currently, in many cases involving women, the diagnosis is achieved through infection screening, which is conducted during prenatal care 3 . In Mexico, it is estimated that 1,500 out of nearly 37,000 cases in women of reproductive age become pregnant each year, 57% of whom receive ART for the first time 4 .…”
Section: Introductionmentioning
confidence: 99%